PENGARUH BRAND CREDIBILITY DAN SELF BRAND CONNECTION TERHADAP LOYALITAS MEREK PADA INDUSTRI FAST FOOD - Harsi, Diyah Ayuni Dwi; Faisal, Aekram (Universitas Of Surakarta, 2023)
This study aims to determine the effect of Brand Credibility and Self Brand Connection on fast food brand loyalty. The purpose of this study was to determine the positive effect of Brand Credibility on Brand Loyalty mediated by Self Brand Connection. Samples were taken with individual criteria, namely people who had bought and consumed fast food products in the last 6 months. This study uses primary data obtained through questionnaires distributed to 211 respondents. Based on the time period, the data collected in this study is cross sectional. The analytical method used is the Structural Equation Model (SEM). The results of this study indicate that brand credibility has a positive (direct) effect on brand loyalty, but brand credibility also has a positive effect on brand loyalty through the role of self-brand connection. This research is expected to provide input to fast food brand managers in Indonesia regarding the factors that need to be considered to achieve and manage consumer loyalty. Among them are Brand Credibility and Self Brand Connection which can help companies achieve brand loyalty.